eu queria saber como calcular está equação que é: -1(x + 4) = 3(x + 5)
Soluções para a tarefa
Respondido por
0
Resposta:
x = - 4,75
Explicação passo-a-passo:
-1(x + 4) = 3(x + 5)
- x - 4 = 3x + 15
- 4 - 15 = 3x + x
- 19 = 4x
4x = - 19
x = - 19/4
x = - 4,75
Respondido por
0
-1x -4 = 3x + 15
-1x -3x = 15 +4
-4x = 19
- 19/4
Explicação passo a passo:
Perguntas interessantes
Química,
7 meses atrás
Matemática,
7 meses atrás
Biologia,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás